Crystal structure and in vitro biological studies of a Pt(II) complex based on gallic acid and triphenylphosphine - Tristão Cruvinel Silva, Raphael; Pereira Silva-Caldeira, Priscila; Manaia Demarqui, Fernanda [UNESP]; Duque Lopes, Carla; de Albuquerque, Sérgio; Rogério Pavan, Fernando [UNESP]; Cristina Pereira-Maia, Elene; Diniz, Renata; de Oliveira, Alberto; de Oliveira Rezende Júnior, Celso; Guerra, Wendell (Elsevier, 2024)
Gallic acid is a natural polyphenol found in a variety of fruits, plants and nuts that has several biological properties, such as anti-oxidant, anti-inflammatory, and antitumor, among other activities. Some studies have proven that metal complexation could be an interesting strategy to enhance its pharmacological activities. Taking that into account, we report here the synthesis, spectral characterization (FTIR, 1H, 13C{1H}, 31P{1H} and 195Pt{1H} NMR), structural analysis, and biological activities of a new platinum(II) complex bearing gallic acid (ga) and triphenylphosphine (PPh3) as ligands. Spectral data suggest that a gallic acid molecule chelates the metal via two deprotonated phenolic oxygen atoms and two monodentate triphenylphosphines complete the coordination sphere. Furthermore, X-ray data support that the platinum(II) ion adopts a slightly distorted square-planar coordination environment. Time-dependent 1H NMR spectra at room temperature suggest that the complex is very stable in DMSO for at least 48 h. Subsequently, the cytotoxic activity of the platinum(II) complex was assessed against chronic myelogenous leukemia cells (k562) and in a non-cancerous cell line (LLCMK2). The complex was more active than gallic acid, cisplatin and carboplatin against the K562 cell line, exhibiting outstanding activity (IC50 = 0.75 μM). When tested against Mycobacterium tuberculosis, the complex showed good activity with a MIC value of 3.75 μg/mL. The results reported here reinforce the antitumor and antimycobacterial potential of metal complexes containing gallic acid and derivatives.
Keywords: Crystal structure; Cytotoxic activity; Gallic acid; Mycobacterium tuberculosis; Platinum(II) complexes